Extracellular Collagen VI Has Prosurvival and Autophagy Instructive Properties in Mouse Fibroblasts - Castagnaro, Silvia; Chrisam, Martina; Cescon, Matilde; Braghetta, Paola; Grumati, Paolo; Bonaldo, Paolo (Frontiers in Physiology, 2018)
Collagen VI (ColVI) is an abundant and distinctive extracellular matrix protein secreted by fibroblasts in different tissues. Human diseases linked to mutations on ColVI genes are primarily affecting skeletal muscle due to non-cell autonomous myofiber defects. To date, it is not known whether and how fibroblast homeostasis is affected by ColVI deficiency, a critical missing information as this may strengthen the use of patients’ fibroblasts for preclinical purposes. Here, we established primary and immortalized fibroblast cultures from ColVI null (Col6a1–/–) mice, the animal model of ColVI-related diseases. We found that, under nutrient-stringent condition, lack of ColVI affects fibroblast survival, leading to increased apoptosis. Moreover, Col6a1–/– fibroblasts display defects in the autophagy/lysosome machinery, with impaired clearance of autophagosomes and failure of Parkin-dependent mitophagy. Col6a1–/– fibroblasts also show an increased activation of the Akt/mTOR pathway, compatible with the autophagy impairment, and adhesion onto purified ColVI elicits a major effect on the autophagic flux. Our findings reveal that ColVI ablation in fibroblasts impacts on autophagy regulation and cell survival, thus pointing at the new concept that this cell type may contribute to the pathological features of ColVI-related diseases.